Acyclovir Levels in Serum and Cerebrospinal Fluid after Oral Administration of Valacyclovir - Lycke, Jan (American Society for Microbiology, 2003)
The possible involvement of herpesviruses in the pathogenesis of multiple sclerosis (MS) was recently investigated in a clinical trial of valacyclovir in patients with MS. As an important part of that survey we performed an independent pharmacokinetic study in order to determine the concentration of acyclovir in cerebrospinal fluid (CSF). The concentrations of acyclovir in serum and CSF were measured at steady state after 6 days of oral treatment with 1,000 mg of valacyclovir three times a day. Samples were obtained from 10 patients with MS. All patients had normal renal function, and none had signs of a damaged blood-CSF barrier. The maximum concentration of acyclovir in serum was reached after 1 to 3 h (mean ± standard deviation [SD], 27.1 ± 5.6 μM), and the minimum concentration in serum was 3.1 ± 1.1 μM (mean ± SD). The acyclovir concentrations in CSF at 2 and 8 h were essentially stable, with the mean ± SD levels being 2.5 ± 0.9 and 2.3 ± 0.7 μM, respectively. Similar levels were recorded in serum and CSF samples from five other MS patients after 6 months of oral treatment with valacyclovir at identical dosages. The area under the concentration-time curve (AUC) for acyclovir in CSF to the AUC for acyclovir in serum (CSF/serum AUC ratio) was approximately 20%. We conclude that the improved bioavailability previously reported for valacyclovir in plasma results in higher concentrations in CSF, while the CSF/serum AUC ratio remains constant.